History as a Source of Competitive Advantages - Thommes, Kirsten; Oertel, Simon (Scandinavian Management Journal)

IccTA: Detecting Inter-Component Privacy Leaks in Android Apps - Li, Li; Bartel, Alexandre; Bissyande, Tegawende F.; Klein, Jacques; Le Traon, Yves; Arzt, Steven; Rasthofer, Siegfried; Bodden, Eric; Octeau, Damien; McDaniel, Patrick (2015 International Conference on Software Engineering (ICSE))
Keywords: CROSSING; ATTRACT; ITSECWEBSITE

Rationalisierung vs. Rationierung Ist die Rationierung unvermeidbar? - Schmitz, Hendrik (Patient Gesundheitswesen – Mission 2030 Unsere gemeinsame Verantwortung die Zukunft zu gestalten)

An LLVM Based Toolchain for Transparent Acceleration of Digital Image Processing Applications using FPGA Overlay Architectures - Funke, Lukas

Instance-Specific Computing in Hard- and Software for Faster Solving of Complex Problems - Löcke, Thomas

Accelerating Programmable Logic Controllers with the use of FPGAs - Wallaschek, Felix

Individual-Level Experience and Organizational-Level Absorptive Capacity: The Special Case of International New Ventures. - Wehner, M C; Schwens, C; Kabst, Rüdiger (Journal of Business Economics.)

Foreign Direct Investment Location Choice of Small- and Medium-Sized Enterprises: The Risk of Value Erosion of Firm-Specific Resources. - Hütt, P; Baum, M; Schwens, C; Kabst, Rüdiger (International Business Review.)

Controllers as Business Partners in Managerial Decision-Making: Attitude, Subjective Norm, and Internal Improvements. - Wolf, S; Weißenberger, B E; Wehner, M C; Kabst, Rüdiger (Journal of Accounting & Organizational Change.)

Interim Management Utilization, Firm Flexibility and its Impact on Firm Performance. - Isidor, R; Schwens, C; Kabst, Rüdiger (International Journal of Human Resources Development and Management.)

Modeling the Impact of Advertisement-Image Congruity on Applicant Attraction. - Baum, M; Schäfer, M; Kabst, Rüdiger (Human Resource Management.)

The effectiveness of recruitment advertisement and recruitment websites: Indirect and interactive effects on applicant attraction. - Baum, M; Kabst, Rüdiger (Human Resource Management (HRM).)

Recruitment Process Outsourcing and Applicant Reactions: When Does Image Make a Difference? - Wehner, M C; Giardini, A; Kabst, Rüdiger (Human Resource Management.)

The effect of culture on the responsiveness of firms to mimetic forces: Imitative foreign joint venture entries into China, 1985–2003. - Li, C; Parboteeah, P (Journal of World Business)

The influence of cultural context on the relationship between gender diversity and team performance: A meta-analysis. - Schneid, M; Isidor, R; Li, C; Kabst, Rüdiger (International Journal of Human Resource Management.)

Participatory Budgeting: Findings from Germany. - Weber, H I; Vogt, S; Eberz-Weber, L M; Steinmetz, Holger; Wagner, S A; Walther, F; Weber, P; Kabst, Rüdiger (International Journal of Public Administration in the Digital Age.)

Requirements for IT Security Metrics - An Argumentation Theory Based Approach - Yasasin, Emrah; Schryen, Guido (23rd European Conference on Information Systems (ECIS 2015))

A Multi-Theoretical Literature Review on Information Security Investments using the Resource-Based View and the Organizational Learning Theory - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (International Conference on Information Systems)
The protection of information technology (IT) has become and is predicted to remain a key economic challenge for organizations. While research on IT security investment is fast growing, it lacks a theoretical basis for structuring research, explaining economic-technological phenomena and guide future research. We address this shortcoming by suggesting a new theoretical model emerging from a multi-theoretical perspective adopt-ing the Resource-Based View and the Organizational Learning Theory. The joint appli-cation of these theories allows to conceptualize in one theoretical model the organiza-tional learning effects that occur when the protection of organizational resources through IT security countermeasures develops over time. We use this model of IT security invest-ments to synthesize findings of a large body of literature and to derive research gaps. We also discuss managerial implications of (closing) these gaps by providing practical ex-amples.
Keywords: Information Security; Investment; Literature review; Resource-based View; Organi-zational Learning Theory; Multi-theoretical Perspective

IT Security Investments Through the Lens of the Resource-Based View: A new Theoretical Model and Literature Review - Weishäupl, Eva; Yasasin, Emrah; Schryen, Guido (23rd European Conference on Information Systems (ECIS 2015))

Towards an Economic Approach to Identity and Access Management Systems Using Decision Theory - Weishäupl, Eva; Kunz, Michael; Yasasin, Emrah; Wagner, Gerit; Prester, Julian; Schryen, Guido; Pernul, Günther (2nd International Workshop on Security in highly connected IT Systems (SHCIS?15))
Nowadays, providing employees with failure-free access to various systems, applications and services is a crucial factor for organizations? success as disturbances potentially inhibit smooth workflows and thereby harm productivity. However, it is a challenging task to assign access rights to employees? accounts within a satisfying time frame. In addition, the management of multiple accounts and identities can be very onerous and time consuming for the responsible administrator and therefore expensive for the organization. In order to meet these challenges, firms decide to invest in introducing an Identity and Access Management System (IAMS) that supports the organization by using policies to assign permissions to accounts, groups, and roles. In practice, since various versions of IAMSs exist, it is a challenging task to decide upon introduction of an IAMS. The following study proposes a first attempt of a decision support model for practitioners which considers four alternatives: Introduction of an IAMS with Role-based Access Control RBAC) or without and no introduction of IAMS again with or without RBAC. To underpin the practical applicability of the proposed model, we parametrize and operationalize it based on a real world use case using input from an expert interview.
Keywords: Identity and Access Management; Economic Decision Making; Information Systems; Information Security Investment; Decision Theory